2019
DOI: 10.3892/ol.2019.10846
|View full text |Cite
|
Sign up to set email alerts
|

High expression level of peptidylprolyl isomerase A is correlated with poor prognosis of liver hepatocellular carcinoma

Abstract: Peptidylprolyl isomerase A (PPIA) has been reported to be correlated with cancer. The present study investigated the prognostic values of PPIA expression levels in cancer by comparing different types of cancer using databases. High expression levels of PPIA were observed in 17 out of 17 cancer types compared with normal adjacent tissues. High expression levels of PPIA were associated with decreased overall survival in low grade glioma, acute myeloid leukemia, lung adenocarcinoma, skin cutaneous melanoma and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
3
8
0
Order By: Relevance
“…Although PPIA is present intracellularly,PPIA can be secreted from cells in response to in ammatory stimuli such as hypoxia, infection, and other oxidative stresses [31]. In our analysis, intense PPIA expression was observed in most of the LUAD tissues, while limited expression was shown in the peritumoral tissues.The high expression of PPIA was related to the poor survival of LUAD patients,which was consistent with the correlation between the overexpression of PPIA and the overall survival of liver hepatocellular carcinoma and colorectal cancer [21,22].ROC curve analysis indicated that PPIA could be a promising diagnostic biomarker to differentiate LUAD from normal tissues.In addition,the progression of LUAD may be associated with the upregulation of PPIA.Notably,the expression of PPIA was positively correlated with high N stage,high pathological stage.Patients with LUAD with higher expression levels of PPIA exhibited signi cantly shorter overall survival times.The increased expression of PPIA in LUAD with pathological stage of III/IV and lymph node metastasis further indicates that PPIA may be involved in the progression and malignant transformation of LUAD. In subgroup analyses, patients of LUAD with high PPIA expression had shorter OS than patients with low PPIA levels and were characterized by TNM stage,pathological stage,male and female,whole age,anatomic neoplasm subdivision of left and peripheral,smoke and non-smoke,smoked for less than 40 years.In M0 stage,the OS was shorter in patients with high expression of PPIA, while in the M1 phase, the epitopes of PPIA were not correlated with OS,which may be related to the aforementioned viewpoint that the anti-tumor properties of CypA may be more effective in the initial stages of cancer development [27].The current results indicated that PPIA may serve as a biomarker for the progress of LUAD.Therefore, in clinical work, LUAD patients with high expression of PPIA have a higher risk of recurrence, and follow-up examinations should be performed more frequently.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although PPIA is present intracellularly,PPIA can be secreted from cells in response to in ammatory stimuli such as hypoxia, infection, and other oxidative stresses [31]. In our analysis, intense PPIA expression was observed in most of the LUAD tissues, while limited expression was shown in the peritumoral tissues.The high expression of PPIA was related to the poor survival of LUAD patients,which was consistent with the correlation between the overexpression of PPIA and the overall survival of liver hepatocellular carcinoma and colorectal cancer [21,22].ROC curve analysis indicated that PPIA could be a promising diagnostic biomarker to differentiate LUAD from normal tissues.In addition,the progression of LUAD may be associated with the upregulation of PPIA.Notably,the expression of PPIA was positively correlated with high N stage,high pathological stage.Patients with LUAD with higher expression levels of PPIA exhibited signi cantly shorter overall survival times.The increased expression of PPIA in LUAD with pathological stage of III/IV and lymph node metastasis further indicates that PPIA may be involved in the progression and malignant transformation of LUAD. In subgroup analyses, patients of LUAD with high PPIA expression had shorter OS than patients with low PPIA levels and were characterized by TNM stage,pathological stage,male and female,whole age,anatomic neoplasm subdivision of left and peripheral,smoke and non-smoke,smoked for less than 40 years.In M0 stage,the OS was shorter in patients with high expression of PPIA, while in the M1 phase, the epitopes of PPIA were not correlated with OS,which may be related to the aforementioned viewpoint that the anti-tumor properties of CypA may be more effective in the initial stages of cancer development [27].The current results indicated that PPIA may serve as a biomarker for the progress of LUAD.Therefore, in clinical work, LUAD patients with high expression of PPIA have a higher risk of recurrence, and follow-up examinations should be performed more frequently.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, this enzyme has been shown to be a key molecule in multiple biological functions, including molecular chaperoning,protein folding,protein tra cking,immune modulation,and cell signaling [6]. Studies have also reported that PPIA is involved in several diseases, including kawasaki disease [7],amyotrophic lateral sclerosis [8],atherosclerosis,myocardial infarction [9],severe sepsis [10],vascular smooth muscle cell disease [11],rheumatoid arthritis and HIV infection [12].Moreover,several studies have shown that PPIA is expressed in some cancers,including lung cancer,nasopharyngeal carcinoma [13],gastric adenocarcinoma [14],thyroid carcinoma [15],neuroblastoma [16],ovarian cancer [17],pancreatic cancer [18],breast cancer,colorectal cancer [19][20],melanoma [21],liver hepatocellular carcinoma [22].Many researchers have assessed PPIA function in cancer.It has been suggested that PPIA plays an important role in the whole pathological process of cancer development.High expression levels of PPIA were associated with decreased overall survival in liver hepatocellular carcinoma,colorectal cancer,low-grade glioma, acute myeloid leukemia.However,in gastric adenocarcinoma, high expression levels of CypA are positively correlated with invasiveness and distant metastasis.Therefore,both low and high expression of PPIA are associated with tumor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…We next focused on CypA, one of the binding partners of CD147, because high expression of both CD147 and CypA has been found to be correlated with a poor prognosis in some malignancies, including esophageal carcinoma, hepatocellular carcinoma, malignant melanoma, and acute myeloid leukemia [17,[34][35][36][37][38]; suggesting the importance of CD147-CypA interactions in malignancies. We found that tumor cells of MF/SS expressed CypA, as well as CD147.…”
Section: Discussionmentioning
confidence: 99%
“…PPIA, also known as cyclophilin A, has roles across a range of biological processes, with essential functions in protein folding and chaperone activity [ 59 ]. PPIA overexpression is reported in various cancer types, its expression influenced by chemotherapy [ 60 , 61 ] and PPIA is a reported target gene of dysregulated miRNA species present in GBM patient plasma [ 62 ]. C3 is a member of the human complement system with key functions in innate immunity.…”
Section: Discussionmentioning
confidence: 99%